Osteopontin – a multifunctional protein and its impact on an insulin resistance development - Musialik, Katarzyna; Skrypnik, Damian; Bogdański, Paweł; Szulińska, Monika (Journal of Medical Science, 2014)
Osteopontin (OPN) is one of the many physiological elements creating human musculoskeletal system. It is suspected that this protein is one of the most important mediators responsible for osseous tissue mass resorption, regulated by parthormon. The origin of its name comes from one of its physiological action – rebuilding of the bone mass structure (osteo – bone, pontin – bridge). Osteopontin fulfils many different actions being secreted by many different types of cells, including macrophages, lymphocytes, epithelial cells, vascular smooth muscle cells, and osteoblasts. OPN plays an important part in inflammatory process. It provokes macrophages and dendritic cells to movement into the destination where inflammatory process takes place. It also stimulates macrophages to interleukin 12 (IL12) and interferon ? (IFN ?) secretion. Increased OPN concentration in blood stream might be regarded as a novel, independent indicator of coronary artery disease. Osteopontin plays an important role in macrophage infiltration of the adipose tissue and at the same time contributes to insulin resistance. Obesity induces chronic, low-grade tissue inflammation. Positive correlation was observed between body mass index (BMI) and number of macrophages accumulated in the fat tissue. Once aroused monocytes infiltrate the adipose tissue, which leads to persisting chronic inflammation. At the same time the excreted by them cytokines may be connected with the mechanisms of obesity-induced insulin resistance.